Clinical impact of extended blood culture examination: Too much of a good thing. Issue 7 (July 2019) - Hagiya, Hideharu; Yoneda, Nanoka; Kimura, Keigo; Mitsui, Tomomi; Ueda, Akiko; Sunada, Atsuko; Nishi, Isao; Nakagami, Futoshi; Rakugi, Hiromi; Tomono, Kazunori
Abstract: Blood culture is the most critical examination for diagnosing bacterial infections. The longer the blood culture incubation period, the higher the chances of identifying bacterial strains. However, unnecessary extension of the incubation period can burden the capacity of the instrument and merely result in the detection of contaminant bacteria having no clinical significance. This study aimed to optimize the blood culture incubation period using the currently available continuous-monitoring automated blood culture instrument. This was a 2-year retrospective study performed at Osaka University Hospital (January 1, 2016 to December 31, 2017). The BD BACTEC™ FX blood culture system (Becton Dickinson, Sparks, MD, USA) and BD BACTEC™ Plus series blood culture bottles were used. All blood cultures were incubated for more than 12 consecutive days. We reviewed the clinical data of cases that tested positive between 6 and 12 days of incubation. During the study period, 14, 822 sets of blood culture were drawn. Of 1751 sets testing positive, 95.7% (1665 sets) became positive within 5 days of incubation. The overall contamination rate (false positives) after 6 days of incubation was 80.2% (69/86 sets). Based on the positive blood culture results, antimicrobials were changed in 7.0% (6/86) of the sets, and a diagnosis of infectious disease was made in only one case. There was no death associated with the extended blood culture results. In conclusion, the clinical impact of extended blood culture incubation for 6 days or more was limited, and a routine extension of the incubation period might be unnecessary.